A Review on Gomutra: Benefactionto Human Beings for Healing by Nature. - Dr. Sandeep Ruplal Jadhao (International Journal of Allied Medical Sciences and Clinical Research, 2020)
Gomutra (Sanskrit: gom?tra;."cowurine") refers to the usage of cow urine for therapeutic purposes in traditional Indian medicine also used as an important component of the mixture called Panchagavya. Ayurveda has also emphasized the importance of Gomutra in the management of various disorders in all treatises. In SushrutaSamhita, the description of Gomutra (Cow urine) has been given as effective substance of animal origin with innumerable therapeutic importance.As per Ayurvedic literatures Gomutra is useful in number of diseases particularly in Gulma, Kushta, ascites, Arbud (cancer) and it is also used along with herbs to treat various diseases like fever, anemia, epilepsy, abdominal pain, various worm infestations, constipation.